Evaluation of the efficiency of interband radiative recombination in high quality Si - Sachenko, A.V.; Kryuchenko, Yu.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 1999)
It is shown theoretically that quantum efficiency of interband radiation in highly purified silicon with low concentration of deep impurities and defects can exceed 10% at room temperatures in the case of negligibly small surface recombination. Dependencies of quantum efficiency on intensity and wavelength of exciting monochromatic light, surface recombination rate and thickness of silicon plate are discussed.